Analysis of Clinical and Pathological Characteristics, Treatment Methods, Survival, and Prognosis of Uterine Papillary Serous Carcinoma. Issue 6 (November 2016) - Solmaz, Ulas; Ekin, Atalay; Mat, Emre; Gezer, Cenk; Dogan, Askin; Biler, Alper; Peker, Nuri; Hasdemir, Pinar Solmaz; Sanci, Muzaffer
Purpose: Uterine papillary serous carcinoma (UPSC) is an atypical variant of endometrial carcinoma with a poor prognosis. It is commonly associated with an increased risk of extrauterine disease. The aim of this study was to investigate clinical and pathological characteristics, therapeutic methods, and prognostic factors in women with UPSC. Methods: All patients who underwent surgery for UPSC at a single high-volume cancer center between January 1995 and December 2010 were retrospectively reviewed. Patients who did not undergo surgical staging and those with mixed tumor histology were excluded. Univariate and multivariate regression models were used to identify the risk factors for overall survival (OS) and progression-free survival (PFS). Results: A total of 46 patients were included, the majority of whom having stage I disease (IA, 13 [28.2%] and IB, 12 [26.7%]). Stages II, III, and IV were identified in 5 (10.9%), 8 (17.4%), and 8 (17.4%) women, respectively. Optimal cytoreduction was obtained in 67.3% of patients. Recurrences developed in 8 (17.4%) patients. Multivariate analysis confirmed that lymphovascular space invasion (LVSI) (odds ratio [OR] 26.83, p = 0.003) was the only independent prognostic factor for OS, whereas LVSI and optimal cytoreduction were found to be independent prognostic factors for PFS (OR 6.91, p = 0.013 and OR 2.69, p = 0.037, respectively). The 5-year overall survival rate was 63%. Conclusions: Our study demonstrated that LVSI is the only independent prognostic factor for OS, whereas LVSI and optimal cytoreduction are independent prognostic factors for PFS in patients with UPSC